Fertility preservation in women undergoing treatment for malignancies: a narrative review - Gupta, Nidhi; Takkar, Navneet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Incidence of cancer is increasing in young patients with simultaneous improvement in survival secondary to advances in cancer treatment. Fertility preservation in this young population is often overlooked in view of priority of cancer treatment, however it is important to avoid distress and provide a good quality of life in these young patients of child bearing age. Fertility might be affected due to systemic therapy like chemotherapy, radiotherapy and surgery involving reproductive organs. Timely referral to reproductive specialist during the narrow window after diagnosis and before starting cytotoxic treatment is required. Embryo and oocyte cryopreservation remains the gold standard with ovarian tissue cryopreservation and re-transplantation undertaken for special situations. Patients undergoing pelvic or abdominal radiotherapy benefit from ovarian transposition and ovarian shielding. Medical gonado-protection with Gonadotropin releasing hormone agonist during cytotoxic chemotherapy remains an area of controversy with conflicting results with recent consensus for use in premenopausal breast cancer patients. Patients requiring surgery for endometrial cancer, ovarian cancer or cervical cancer may be considered for conservative management including conservative surgery for early stage cancers with specific indications with the intent to allow patients to complete family. Adequate patient counselling for oncology outcomes and fertility preservation are required to enable the patients to take informed decisions to choose the unconventional path of cancer management and uncertainty involving pregnancy and live births.